Methylene blue adsorption onto modified lignin from sugar cane bagasse - Consolin-Filho, Nelson; Venancio, Everaldo Carlos; Barriquello, Marcilene Ferrari; Hechenleitner, Ana Adelina Winkler; Pineda, Edgardo Afonso Gómez (Eclética Química, 2007)
The adsorption kinetics and equilibrium of methylene blue (MB) onto reticulated formic lignin (RFL) from sugar cane bagasse was studied. The adsorption process is pH, temperature and ionic strength (μ) dependent and obeys the Langmuir model. Conditions for higher adsorption rate and capacity were determined. The faster adsorption (12 hours) and higher adsorption capacity (34.20 mg.g -1 ) were observed at pH = 5.8 (acetic acid-sodium acetate aqueous buffer), 50 °C and 0.1 ionic strength. Under temperature (50 °C) control and occasional mechanical stirring it took from 1 to 10 days to reach the equilibrium.